Plants monitor the integrity of their barrier by sensing gas diffusion - Hiroyuki Iida; Isidro Abreu; Jennifer López Ortiz; Lucas León Peralta Ogorek; Vinay Shukla; Meeri Mäkelä; Munan Lyu; Alexey Shapiguzov; Francesco Licausi; Ari Pekka Mähönen (Nature, 2025)
Abstract Barrier tissues isolate organisms from their surrounding environment. Maintaining the integrity of the tissues is essential for this function. In many seed plants, periderm forms as the outer barrier during secondary growth to prevent water loss and pathogen infection1. The periderm is regenerated when its integrity is lost following injury; however, the underlying mechanism remains largely unknown, despite its importance for plant survival. Here we report that periderm integrity in Arabidopsis roots is sensed by diffusion of the gases ethylene and oxygen. Following injury of the periderm, ethylene leaks out through the wound and oxygen enters, resulting in attenuation of ethylene signalling and hypoxia signalling. This condition promotes periderm regeneration in the root. When regeneration is complete and barrier integrity is re-established, pre-injury levels of ethylene and hypoxia signalling are regained. Gas diffusion monitoring is also used to re-establish the barrier in inflorescence stems after the epidermis is injured. We thus propose that gas diffusion is used by plants as a general principle to monitor and re-establish barrier integrity.